Climate controls on carbon accumulation in peatlands of Northeast China - Xing, Wei; Bao, Kunshan; Gallego-Sala, Angela V.; Charman, Dan J.; Zhang, Zhenqing; Gao, Chuanyu; Lu, Xianguo; Wang, Guoping (Quaternary science reviews, 2015)
Peatlands contain around one third of the global soil carbon (C) and play an important role in the C cycle. In particular, the response of the productivity-decay balance to climate variability is critical for understanding both the past and future global C cycle. Most studies of peatland C dynamics have been carried out on boreal and subarctic peatlands, where climate models predict a greater increase in temperature compared to the global average. Less is known about peatlands at lower latitudes, yet there are significant peatland C stocks in these regions that may be more vulnerable to future climate change because they are closer to the climatic limit of peatland distribution. Northeast China is China's largest wetland region, with extensive peatlands in mountain regions and across the plains. Here, we used core data from 134 peatland sites to quantify the C accumulation rate over different timescales and estimate C storage across northeast China. The results show that the Holocene long-term apparent rate of C accumulation (LORCA) ranged from 5.74 to 129.31 g C m−2 yr−1, with a mean rate of 33.66 g C m−2 yr−1. The total wetland area and C storage within this region is 82,870 km2 and 4.34 Gt C, and about 80% of the C is contained in mountain peatlands. We find that total C accumulated over the last 2000 years is linearly related to photosynthetically active radiation over the growing season, supporting the hypothesis that rates of net primary productivity (NPP) are more important than decomposition rates in determining long-term C accumulation. Although peatlands in northeast China are close to the southern limit of major peatland extent, our data suggest that future warming will lead to greater future C accumulation, as long as moisture balance or cloudiness do not become limiting factors. •Northeast China shows a high C accumulation rate during the Holocene.•The current peatland area is 82,900 km2 and contains ∼4.34 Gt C in northeast China.•C accumulation over the last 2000 years is linearly related to the PAR0.